Influence of solar extreme ultraviolet radiations on artificial very-low-frequency waves in near-earth space - K. X. Cheng; L. Y. Li; L. Yang; J. B. Cao; J. Yu; S. F. Zhao (Scientific Reports)
Abstract Ground-based very low frequency (VLF) transmitter waves (3 – 30 kHz) can cause the precipitation loss of high-energy electrons in Earth’s radiation belts. Although the propagation and attenuation of aabrtificial VLF waves have been studied for more than half a century, it is not clear whether solar extreme ultraviolet (EUV) radiations can modify the VLF wave intensity in inner radiation belt and slot region (L ~ 1.1 – 3RE). Here, by analyzing satellite observations and quantitative calculations, we find that the enhanced solar EUV radiations cause global attenuation of the artificial VLF waves radiated from low-latitude transmitters (λ < 44.2° or L < 1.8 RE), whereas those waves radiated from middle-latitude transmitters (λ > 44.2° or L > 1.8 RE) weaken slightly around noon. Under high solar EUV radiations, the large attenuation of artificial VLF waves in the low L region is due to enhanced collisional damping of ionospheric plasmas at low latitudes.